Web-Based E-Learning Information System with Multi-Role Monitoring Feature at SMP Ibrahimy 2 Sukorejo - Rosita Natania Maulani; Achmad Baijuri; Firman Santoso (Universitas Muhammadiyah Jember, 2026)
Learning at SMP Ibrahimy 2 Sukorejo is still conducted conventionally, resulting in limited material access outside school hours and minimal learning monitoring. This study designs and implements a web-based e-learning information system using the Waterfall method. The system accommodates five actors (Admin, Teacher, Student, Class Teacher, Curriculum Vice Principal), with novelty in multi-role monitoring features and integration of five roles in a single platform. Main features include learning material management, online assignment submission, UTS/UAS evaluation with automatic grade calculation (Final Grade = (Assignment Score + Exam Score) / 2), real-time notifications, and per-role monitoring dashboards. Functional testing using Black Box Testing on 20 scenarios across 8 modules yielded a 100% success rate (20/20 scenarios matched expected outcomes). Usability testing using System Usability Scale (SUS) with 15 respondents produced a mean score of 81.3, categorized as Excellent. The system was successfully implemented as an integrated digital platform supporting the teaching and learning process at SMP Ibrahimy 2 Sukorejo.